2004
DOI: 10.1207/s15516709cog2803_4
|View full text |Cite
|
Sign up to set email alerts
|

Artificial syntactic violations activate Broca's region

Abstract: In the present study, using event-related functional magnetic resonance imaging, we investigated a group of participants on a grammaticality classification task after they had been exposed to well-formed consonant strings generated from an artificial regular grammar. We used an implicit acquisition paradigm in which the participants were exposed to positive examples. The objective of this study was to investigate whether brain regions related to language processing overlap with the brain regions activated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
188
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 107 publications
(232 citation statements)
references
References 123 publications
39
188
2
3
Order By: Relevance
“…Here we only give a brief summary of the most important results. Consistent with previous findings (Forkstam et al, 2006;Petersson et al, 2004) the overall correct classification performance was clearly above chance (73 ± 16% correct, T(31) = 7.7, P < .001). The analysis of hit rate showed that the subjects were sensitive to the grammaticality of the items (F(2, 62) = 26, P < .001).…”
Section: Behavioral Characterizationsupporting
confidence: 91%
See 4 more Smart Citations
“…Here we only give a brief summary of the most important results. Consistent with previous findings (Forkstam et al, 2006;Petersson et al, 2004) the overall correct classification performance was clearly above chance (73 ± 16% correct, T(31) = 7.7, P < .001). The analysis of hit rate showed that the subjects were sensitive to the grammaticality of the items (F(2, 62) = 26, P < .001).…”
Section: Behavioral Characterizationsupporting
confidence: 91%
“…The size of this region was chosen because we used a spatial filter kernel of FWHM = 10 mm, which roughly corresponds to the spatial scale of localization precision in group FMRI studies (Brett, Johnsrude, & Owen, 2002;Petersson, Nichols, Poline, & Holmes, 1999), including language (Hagoort, 2005;Petersson et al, 2004). In this analysis we used small volume correction based on the family-wise error (FWE) corrected for multiple non-independent comparisons based on smooth 3D random field theory (Adler & Taylor, 2007).…”
Section: Mr Image Preprocessing and Statistical Analysismentioning
confidence: 99%
See 3 more Smart Citations